Preparation and application of nano cellulose / nano magnesium oxide anhydrous paper deacidification and reinforcement composite reagent

Through the deacidification and reinforcement composite reagent of nanocellulose/nanomagnesium oxide anhydrous paper, the problems of paper cultural relics decreased and dried deformation after water treatment were solved, the pH value and mechanical properties of the paper were improved, and the effect of cultural relics protection was achieved. .

CN119308177APending Publication Date: 2025-01-14QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411705402.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing deacidification and reinforcement technology of paper cultural relics has problems such as the decrease in paper strength, dry deformation and water-soluble dye diffusion after water treatment, making it difficult to effectively protect aging paper cultural relics.

Method used

Using nanocellulose/nanomagnesium oxide anhydrous paper deacidification reinforcement composite reagent, anhydrous system was prepared by mixing nanomagnesium oxide with nanocellulose aqueous dispersion and adding organic solvents to remove moisture by evaporation, and anhydrous system was prepared for the The aging paper is coated to improve the pH value and mechanical properties of the paper.

Benefits of technology

It has achieved the improvement of the service life and mechanical properties of the paper, simple operation, low cost, green and environmentally friendly, and avoids the problems of reduced strength and dry deformation caused by water treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119308177A_ABST
    Figure CN119308177A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ancient book protection, and particularly relates to preparation and application of a nano cellulose / nano magnesium oxide anhydrous paper deacidification and reinforcement composite reagent. The preparation method comprises the following steps: weighing a prepared nano cellulose aqueous dispersion in a beaker, adding nano magnesium oxide into the dispersion, uniformly mixing, adding dimethyl sulfoxide into the beaker, stirring for 1 hour to form a uniformly dispersed mixture, stirring the mixture in a water bath of 100 DEG C for 1 hour, steaming out water, and drying to obtain the nano magnesium oxide / dimethyl sulfoxide composite material. And stirring until a uniformly dispersed anhydrous organic dispersion system is obtained. And quantitatively coating the surface of the aged paper by adopting a coating method, and then transferring the aged paper to a drying oven for drying to obtain the deacidified and reinforced paper. And then detecting the pH value and the physical property of the aged paper and the deacidified and reinforced paper. The method is low in cost, simple to operate, green and environment-friendly, and can effectively improve the performance of the aged paper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of paper cultural relic protection, relates to a method for protecting paper fibers, and specifically relates to the preparation of a nanocellulose / nanomagnesium oxide anhydrous paper deacidification and reinforcement composite reagent and a method for deacidification and reinforcement of aged paper. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Paper documents are an important carrier of human civilization and have multiple valuable attributes such as academic, artistic and historical. The main component of paper documents is cellulose, and contains a small amount of hemicellulose and lignin, fillers, inks and pigments. The use of acid additives in the modern papermaking industry, as well as factors such as air pollution and improper storage, have caused paper documents to become acidified, brittle and powdered, seriously shortening their lifespan. Therefore, exploring efficient and low-damage methods to repair paper documents has become a topic that needs to be focused on.

[0004] The non-aqueous phase deacidification system with alkaline nanoparticles as deacidification agents has become a hot topic in academic application research at home and abroad. Commonly used nanoparticles include nanomagnesium oxide, nanocalcium hydroxide, nanotitanium dioxide, etc. Nanomagnesium oxide (MgO) has relatively suitable alkalinity. It can effectively remove acidic substances in paper by preparing it into a deacidification solution and treating paper. Nanoscale MgO particles are small enough to completely penetrate and penetrate into the interior of the paper. The electrostatic effect will cause these particles to adhere tightly to the surface texture and internal fibers of the paper. These nanoscale MgO particles have a high surface area and are highly surface active. They can react with the water adsorbed in the paper to generate alkaline Mg(OH)2, thereby effectively removing the acid in the paper and preventing the hydrolysis of paper artifacts. At the same time, they can be used as alkaline storage for paper, and can exist in the paper for a long time to neutralize the acid and extend the shelf life of the paper.

[0005] Nanocellulose has been widely studied in recent years due to its high purity and crystallinity, as well as good mechanical properties. Nanocellulose not only has the characteristics of natural cellulose such as being renewable and biodegradable, but also has a series of advantages such as large specific surface area, high strength, high Young's modulus, high transparency, and low thermal expansion coefficient, which are consistent with the fiber structure of paper. These advantages make it have broad application prospects in the protection of paper cultural relics. At present, there have been a small number of studies on the protection of paper cultural relics by nanocellulose, but the existing research mainly uses nanocellulose water dispersion system to treat paper. Water dispersion treatment of paper cultural relics has the following disadvantages:

[0006] (1) After being treated with a large amount of water, paper artifacts, especially those with low strength, will rapidly lose strength when exposed to water, and may even turn into pulp;

[0007] (2) After water treatment, the paper will deform when it dries, changing the original state of the cultural relic;

[0008] (3) Some paper artifacts contain words or patterns written or drawn with water-soluble dyes, which will diffuse when exposed to water. Summary of the invention

[0009] In order to solve the shortcomings of the existing paper deacidification and reinforcement technology, the purpose of the present invention is to provide a preparation method of a nanocellulose / nanomagnesium oxide anhydrous paper deacidification and reinforcement composite reagent and a method for deacidification and reinforcement of aged paper. The method of the present invention is simple to operate, low in cost, green and environmentally friendly, and can effectively improve the performance of aged paper.

[0010] In order to achieve the above object, the present invention adopts the following technical solution:

[0011] The first aspect of the present invention provides a method for preparing a nanocellulose / nanomagnesium oxide anhydrous paper deacidification and reinforcement composite reagent, comprising:

[0012] The nano-magnesium oxide and the nano-cellulose aqueous dispersion are uniformly mixed, and then an organic solvent is added to prepare a dispersion system;

[0013] The water in the dispersed system is removed by evaporation to obtain an anhydrous system.

[0014] In some embodiments, the mass ratio of nano-cellulose to nano-magnesium oxide is 1-5:1-2.

[0015] In some embodiments, the organic solvent is dimethyl sulfoxide, which can make the nanocellulose disperse better and have strong permeability and high stability.

[0016] In some embodiments, the evaporation temperature is 100°C-105°C.

[0017] In some embodiments, the solid content of the nanocellulose aqueous dispersion is 1%-1.5%.

[0018] The second aspect of the present invention provides a nano-cellulose / nano-magnesium oxide anhydrous paper deacidification and reinforcement composite reagent prepared by the above method.

[0019] The third aspect of the present invention provides a method for deacidifying and strengthening aged paper using the above-mentioned composite reagent, comprising:

[0020] The aged paper is coated with the composite reagent and dried to obtain the product.

[0021] In some embodiments, the coating amount is 100-120 g / m 2 .

[0022] In some embodiments, the coating is performed at least twice.

[0023] In some embodiments, the drying temperature is 60°C-65°C.

[0024] Beneficial effects of the present invention

[0025] (1) The present invention uses a nanocellulose and nanomagnesium oxide composite system to treat aged paper, thereby increasing the pH value of the paper and prolonging its service life. At the same time, the use of this system for treatment can also improve the mechanical properties of the aged paper, thereby achieving the purpose of cultural relic protection.

[0026] (2) The present invention is simple to operate, green and environmentally friendly, and uses nanocellulose with low cost and environmental friendliness, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.

[0028] Figure 1 This is the SEM image of the paper that has not been aged after papermaking;

[0029] Figure 2 This is the SEM image of the paper after aging;

[0030] Figure 3 This is the SEM image of aged paper coated with nanocellulose and nanomagnesium oxide in a mass ratio of 1:1 in an organic anhydrous system;

[0031] Figure 4 This is the SEM image of aged paper coated with nanocellulose and nanomagnesium oxide in a mass ratio of 3:2 in an organic anhydrous system;

[0032] Figure 5 This is the SEM image of aged paper coated with nanocellulose and nanomagnesium oxide in a mass ratio of 2:1 in an organic anhydrous system;

[0033] Figure 6 This is the SEM image of aged paper coated with nanocellulose and nanomagnesium oxide in a mass ratio of 5:2 in an organic anhydrous system;

[0034] Figure 7 This is a stability diagram of the dispersion of nanocellulose and nanomagnesium oxide prepared in the above mass ratio in an organic anhydrous system after long-term storage. DETAILED DESCRIPTION

[0035] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0036] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0037] In the following examples and comparative examples, the pine pulp and bleached acacia hardwood pulp used are both commercially available products.

[0038] Example 1

[0039] (1) Preparation and aging of base paper: Pine pulp and bleached acacia hardwood pulp were mixed evenly at a mass ratio of 1:9 and made into paper by a papermaking machine. After acidification, the paper was hung in a BHO-401A dry heat aging test chamber for accelerated aging according to GB / T 464-2008 "Accelerated dry heat aging of paper and paperboard", with the aging temperature set at 105°C and the aging time set at 72h.

[0040] (2) Preparation of nanocellulose: The cellulose raw material is subjected to mechanical grinding, shearing, ultrafine grinding and other treatments to obtain a nanocellulose aqueous dispersion with a solid content of 1%.

[0041] (3) Preparation of anhydrous organic dispersion system: Weigh 15 g of the prepared nanocellulose aqueous dispersion into a beaker, add 0.15 g of nanomagnesium oxide to the dispersion and mix evenly so that the mass ratio of nanocellulose to nanomagnesium oxide is 1:1, then add 30 g of dimethyl sulfoxide to the beaker and stir for 1 h to form a uniformly dispersed mixture, then stir the mixture in a 100°C water bath for 1 h to evaporate the water until a uniformly dispersed anhydrous organic dispersion system is obtained.

[0042] (4) Deacidification and reinforcement treatment: The anhydrous organic dispersion system is evenly coated on the aged paper and placed in a 60°C oven for drying. The quantitative amount is 100 g / m 2 Apply twice to ensure that both sides of the aged paper are evenly coated.

[0043] (5) pH value detection: According to the international standard ISO6588, add 250 mL of cold distilled water to 5 g of paper sample and leave it for about 3 hours. After the paper is completely immersed, use a pH meter to measure the pH value of the water, that is, to measure the concentration of hydrogen ions dissolved in the water as the pH value of the paper. The pH values ​​of the aged paper prepared in this example and the aged paper after deacidification and reinforcement were 4.3-4.5 and 9.7-9.9, respectively.

[0044] (6) Physical property testing: Cut the deacidified and reinforced paper into paper samples with a specific length and width of 15 mm, and measure the tensile strength using a tensile strength tester. Calculate the tensile index to evaluate the performance of the paper. Definition of tensile index: The tensile index is the tensile property of the paper expressed in terms of the tensile force per unit width and unit quantitative sample, expressed in Nm / g, and the calculation formula is as follows: X = F×W0×b0÷(W×b) Unit of tensile index: Nm / g In the formula: X-tensile index; F-tensile force (N); W-sample quantity (g / m 2 ); W0 -100 / m 2 ; b- sample width (15 mm); b0-100 mm. The tensile indexes of the aged paper and the deacidified and reinforced paper prepared in this embodiment are 7.2-7.3 and 9.1-9.2, respectively.

[0045] The deacidified and reinforced paper is cut into paper samples of specific length and width, and the tear resistance is measured by a tear tester. The tear resistance index is calculated to evaluate the performance of the paper. Tear index: The average internal tear strength divided by the basis weight is the tear index, expressed in mN·m 2 / g. Calculation formula: X = a / w Where: X-tear index, mN·m 2 / g; a-tear strength, mN (gf); w-quantity according to GB451, g / m 2 The tear resistance indexes of the aged paper and the deacidified and reinforced paper prepared in this embodiment are 77-78 and 91-92 respectively.

[0046] Example 2

[0047] (1) Preparation and aging of base paper: Pine pulp and bleached acacia hardwood pulp were mixed evenly at a mass ratio of 1:9 and made into paper by a papermaking machine. After acidification, the paper was hung in a BHO-401A dry heat aging test chamber for accelerated aging according to GB / T 464-2008 "Accelerated dry heat aging of paper and paperboard", with the aging temperature set at 105°C and the aging time set at 72h.

[0048] (2) Preparation of nanocellulose: The cellulose raw material is subjected to mechanical grinding, shearing, ultrafine grinding and other treatments to obtain a nanocellulose aqueous dispersion with a solid content of 1%.

[0049] (3) Preparation of anhydrous organic dispersion system: Weigh 15 g of the prepared nanocellulose aqueous dispersion into a beaker, add 0.1 g of nanomagnesium oxide to the dispersion and mix evenly so that the mass ratio of nanocellulose to nanomagnesium oxide is 3:2, then add 30 g of dimethyl sulfoxide to the beaker and stir for 1 h to form a uniformly dispersed mixture, then stir the mixture in a 100°C water bath for 1 h to evaporate the water until a uniformly dispersed anhydrous organic dispersion system is obtained.

[0050] (4) Deacidification and reinforcement treatment: The anhydrous organic dispersion system is evenly coated on the aged paper and placed in a 60°C oven for drying. The quantitative amount is 100 g / m 2 Apply twice to ensure that both sides of the aged paper are evenly coated.

[0051] (5) pH value detection: According to the international standard ISO6588, add 250 mL of cold distilled water to 5 g of paper sample and leave it for about 3 hours. After the paper is completely immersed, use a pH meter to measure the pH value of the water, that is, to measure the concentration of hydrogen ions dissolved in the water as the pH value of the paper. The pH values ​​of the aged paper prepared in this example and the aged paper after deacidification and reinforcement were 4.2-4.4 and 9.5-9.9, respectively.

[0052] (6) Physical property testing: Cut the deacidified and reinforced paper into paper samples with a specific length and width of 15 mm, and measure the tensile strength using a tensile strength tester. Calculate the tensile index to evaluate the performance of the paper. Definition of tensile index: The tensile index is the tensile property of the paper expressed in terms of the tensile force per unit width and unit quantitative sample, expressed in Nm / g, and the calculation formula is as follows: X = F×W0×b0÷(W×b) Unit of tensile index: Nm / g In the formula: X-tensile index; F-tensile force (N); W-sample quantity (g / m 2 ); W0 -100 / m 2 ; b- sample width (15 mm); b0-100 mm. The tensile indexes of the aged paper and the deacidified and reinforced paper prepared in this embodiment are 7.2-7.4 and 10.6-10.9 respectively.

[0053] The deacidified and reinforced paper is cut into paper samples of specific length and width, and the tear resistance is measured by a tear tester. The tear resistance index is calculated to evaluate the performance of the paper. Tear index: The average internal tear strength divided by the basis weight is the tear index, expressed in mN·m 2 / g. Calculation formula: X = a / w Where: X-tear index, mN·m 2 / g; a-tear strength, mN (gf); w-quantity according to GB451, g / m 2 The tear resistance indexes of the aged paper and the deacidified and reinforced paper prepared in this embodiment are 77-78 and 96-98 respectively.

[0054] Example 3

[0055] (1) Preparation and aging of base paper: Pine pulp and bleached acacia hardwood pulp were mixed evenly at a mass ratio of 1:9 and made into paper by a papermaking machine. After acidification, the paper was hung in a BHO-401A dry heat aging test chamber for accelerated aging according to GB / T 464-2008 "Accelerated dry heat aging of paper and paperboard", with the aging temperature set at 105°C and the aging time set at 72h.

[0056] (2) Preparation of nanocellulose: The cellulose raw material is subjected to mechanical grinding, shearing, ultrafine grinding and other treatments to obtain a nanocellulose aqueous dispersion with a solid content of 1%.

[0057] (3) Preparation of anhydrous organic dispersion system: Weigh 15 g of the prepared nanocellulose aqueous dispersion into a beaker, add 0.075 g of nanomagnesium oxide to the dispersion and mix evenly so that the mass ratio of nanocellulose to nanomagnesium oxide is 2:1, then add 30 g of dimethyl sulfoxide to the beaker and stir for 1 h to form a uniformly dispersed mixture, then stir the mixture in a 100°C water bath for 1 h to evaporate the water until a uniformly dispersed anhydrous organic dispersion system is obtained.

[0058] (4) Deacidification and reinforcement treatment: The anhydrous organic dispersion system is evenly coated on the aged paper and placed in a 60°C oven for drying. The quantitative amount is 100 g / m 2 Apply twice to ensure that both sides of the aged paper are evenly coated.

[0059] (5) pH value detection: According to the international standard ISO6588, add 250 mL of cold distilled water to 5 g of paper sample and leave it for about 3 hours. After the paper is completely immersed, use a pH meter to measure the pH value of the water, that is, to measure the concentration of hydrogen ions dissolved in the water as the pH value of the paper. The pH values ​​of the aged paper prepared in this example and the aged paper after deacidification and reinforcement were 4.3-4.5 and 9.8-10.2, respectively.

[0060] (6) Physical property testing: Cut the deacidified and reinforced paper into paper samples with a specific length and width of 15 mm, and measure the tensile strength using a tensile strength tester. Calculate the tensile index to evaluate the performance of the paper. Definition of tensile index: The tensile index is the tensile property of the paper expressed in terms of the tensile force per unit width and unit quantitative sample, expressed in Nm / g, and the calculation formula is as follows: X = F×W0×b0÷(W×b) Unit of tensile index: Nm / g In the formula: X-tensile index; F-tensile force (N); W-sample quantity (g / m 2 ); W0 -100 / m 2 ; b- sample width (15 mm); b0-100 mm. The tensile indexes of the aged paper and the deacidified and reinforced paper prepared in this embodiment are 7.3-7.4 and 18.7-18.9 respectively.

[0061] The deacidified and reinforced paper is cut into paper samples of specific length and width, and the tear resistance is measured by a tear tester. The tear resistance index is calculated to evaluate the performance of the paper. Tear index: The average internal tear strength divided by the basis weight is the tear index, expressed in mN·m 2 / g. Calculation formula: X = a / w Where: X-tear index, mN·m 2 / g; a-tear strength, mN (gf); w-quantity according to GB451, g / m 2 The tear resistance indexes of the aged paper and the deacidified and reinforced paper prepared in this embodiment are 77-78 and 98-100 respectively.

[0062] Example 4

[0063] (1) Preparation and aging of base paper: Pine pulp and bleached acacia hardwood pulp were mixed evenly at a mass ratio of 1:9 and made into paper by a papermaking machine. After acidification, the paper was hung in a BHO-401A dry heat aging test chamber for accelerated aging according to GB / T 464-2008 "Accelerated dry heat aging of paper and paperboard", with the aging temperature set at 105°C and the aging time set at 72h.

[0064] (2) Preparation of nanocellulose: The cellulose raw material is subjected to mechanical grinding, shearing, ultrafine grinding and other treatments to obtain a nanocellulose aqueous dispersion with a solid content of 1%.

[0065] (3) Preparation of anhydrous organic dispersion system: Weigh 15 g of the prepared nanocellulose aqueous dispersion into a beaker, add 0.06 g of nanomagnesium oxide to the dispersion and mix evenly so that the mass ratio of nanocellulose to nanomagnesium oxide is 5:2, then add 30 g of dimethyl sulfoxide to the beaker and stir for 1 h to form a uniformly dispersed mixture, then stir the mixture in a 100°C water bath for 1 h to evaporate the water until a uniformly dispersed anhydrous organic dispersion system is obtained.

[0066] (4) Deacidification and reinforcement treatment: The anhydrous organic dispersion system is evenly coated on the aged paper and placed in a 60°C oven for drying. The quantitative amount is 100 g / m 2 Apply twice to ensure that both sides of the aged paper are evenly coated.

[0067] (5) pH value detection: According to the international standard ISO6588, add 250 mL of cold distilled water to 5 g of paper sample and leave it for about 3 hours. After the paper is completely immersed, use a pH meter to measure the pH value of the water, that is, to measure the concentration of hydrogen ions dissolved in the water as the pH value of the paper. The pH values ​​of the aged paper prepared in this example and the aged paper after deacidification and reinforcement were 4.5-4.6 and 9.6-9.8, respectively.

[0068] (6) Physical property testing: Cut the deacidified and reinforced paper into paper samples with a specific length and width of 15 mm, and measure the tensile strength using a tensile strength tester. Calculate the tensile index to evaluate the performance of the paper. Definition of tensile index: The tensile index is the tensile property of the paper expressed in terms of the tensile force per unit width and unit quantitative sample, expressed in Nm / g, and the calculation formula is as follows: X = F×W0×b0÷(W×b) Unit of tensile index: Nm / g In the formula: X-tensile index; F-tensile force (N); W-sample quantity (g / m 2 ); W0 -100 / m 2 ; b- sample width (15 mm); b0-100 mm. The tensile indexes of the aged paper and the deacidified and reinforced paper prepared in this embodiment are 7.3-7.5 and 17.7-18.5 respectively.

[0069] The deacidified and reinforced paper is cut into paper samples of specific length and width, and the tear resistance is measured by a tear tester. The tear resistance index is calculated to evaluate the performance of the paper. Tear index: The average internal tear strength divided by the basis weight is the tear index, expressed in mN·m 2 / g. Calculation formula: X = a / w Where: X-tear index, mN·m 2 / g; a-tear strength, mN (gf); w-quantity according to GB451, g / m 2 The tear resistance indexes of the aged paper and the deacidified and reinforced paper prepared in this example are 77-78 and 93-95 respectively.

[0070] Comparative Example 1

[0071] The difference from Example 1 is that no organic solvent is added and the aged paper is coated with a water dispersion system.

[0072] The preparation method comprises: weighing 15 g of the prepared nanocellulose aqueous dispersion into a beaker, adding 0.1 g of nanomagnesium oxide to the dispersion and mixing evenly so that the mass ratio of nanocellulose to nanomagnesium oxide is 3:2, then adding 30 g of water into the beaker, and stirring for 1 hour to form a uniformly dispersed mixture.

[0073] The test results show that the size of the aged paper coated with this dispersion system shrinks and changes. The evaporation of water causes uneven drying and takes away the moisture in the base paper, causing the size to shrink.

[0074] Comparative Example 2

[0075] The difference from Example 1 is that the water is not evaporated and the aged paper is coated with an organic-water mixed dispersion system.

[0076] The preparation method comprises: weighing 15 g of the prepared nanocellulose aqueous dispersion into a beaker, adding 0.1 g of nanomagnesium oxide to the dispersion and mixing evenly so that the mass ratio of nanocellulose to nanomagnesium oxide is 3:2, then adding 30 g of dimethyl sulfoxide into the beaker, and stirring for 1 hour to form a uniformly dispersed mixture.

[0077] The test results show that the size of aged paper after coating with this dispersion system shrinks slightly, and this dispersion system has lower deacidification efficiency, slower speed and more complicated operation than pure organic system.

[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a nanocellulose / nanomagnesium oxide anhydrous paper deacidification and reinforcement composite reagent, characterized in that: include: The nano-magnesium oxide and the nano-cellulose aqueous dispersion are uniformly mixed, and then an organic solvent is added to prepare a dispersion system; The water in the dispersed system is removed by evaporation to obtain an anhydrous system.

2. The method for preparing the nanocellulose / nanomagnesium oxide anhydrous paper deacidification and reinforcement composite reagent according to claim 1, characterized in that: The mass ratio of the nano cellulose to the nano magnesium oxide is 1-5:1-2.

3. The method for preparing the nanocellulose / nanomagnesium oxide anhydrous paper deacidification and reinforcement composite reagent according to claim 1, characterized in that: The organic solvent is dimethyl sulfoxide.

4. The method for preparing the nanocellulose / nanomagnesium oxide anhydrous paper deacidification and reinforcement composite reagent according to claim 1, characterized in that: The evaporation temperature is 100°C-105°C.

5. The method for preparing the nanocellulose / nanomagnesium oxide anhydrous paper deacidification and reinforcement composite reagent according to claim 1, characterized in that: The solid content of the nanocellulose aqueous dispersion is 1%-1.5%.

6. A nanocellulose / nanomagnesium oxide anhydrous paper deacidification and reinforcement composite reagent prepared by the method according to any one of claims 1 to 5.

7. A method for deacidifying and reinforcing aged paper using the composite reagent according to claim 6, characterized in that: include: The composite reagent according to claim 6 is applied to aged paper and dried to obtain the product.

8. The method for deacidifying and reinforcing aged paper using a composite reagent as claimed in claim 7, characterized in that: The coating amount is 100-120g / m 2 .

9. The method for deacidifying and reinforcing aged paper using a composite reagent as claimed in claim 7, characterized in that: The coating times are at least twice.

10. The method for deacidifying and strengthening aged paper using a composite reagent as claimed in claim 7, characterized in that: The drying temperature is 60°C-65°C.

Citation Information

Patent Citations

  • Water-free deacidification nano-solution and preparation method thereof

    CN109989295A

  • Nano-cellulose / nano-zinc oxide multifunctional protection liquid, preparation method thereof and method for protecting paper documents

    CN111270559A

  • Organic phase deacidification enhanced repair liquid as well as preparation method and application thereof

    CN115874485A

  • Method for deacidifying vaterite type calcium carbonate and modified nanocellulose and reinforcing and enhancing paper

    CN118127855A

  • Organic solvent dispersion method of cellulose nanofiber and apparatus of the same

    JP2020183483A